Inhibition of mild steel corrosion in acid solution by Pheniramine drug: Experimental and theoretical study - Ahamad I.; Prasad R.; Quraishi M.A. (My University, 2025)
Inhibition of mild steel corrosion in 1 M HCl solution by Pheniramine drug was studied using weight loss, electrochemical impedance spectroscopy, linear polarization resistance, and potentiodynamic polarization measurements. The values of activation energy (Ea) and different thermodynamic parameters such as adsorption equilibrium constant (Kads), free energy of adsorption (Δ Gads°), adsorption enthalpy (Δ Hads°) and adsorption entropy (Δ Sads°) were calculated and discussed. The adsorption process of studied drug on mild steel surface obeys the Langmuir adsorption isotherm. Potentiodynamic polarization measurements showed that Pheniramine is mixed-type inhibitor. Further, theoretical calculations were carried out and relations between computed parameters and experimental inhibition efficiency were discussed. © 2010 Elsevier Ltd. All rights reserved.